Comparison of intergenerational transmission of gender roles between single-parent families and two-parent families: The influence of parental child-rearing gender-role attitudes. (June 2021) - Yang, Mengping; Chen, I-Jun; Song, Yunping; Wang, Xiaoxiao
Highlights: Gender roles of two generations are similar in both single- and two-parent families. There are significant differences in the proportion of undifferentiated and androgynous in different family structures. Family SES, family structure and parental child-rearing gender-role attitudes significantly positively affect the intergenerational transmission of gender roles (ITGR). The gender and age of children significantly negatively affect the ITGR. Parental child-rearing gender-role attitudes play a partial mediating role between family structure and ITGR. Abstract: The characteristics of parents' gender roles directly impact the children's gender roles, thus forming intergenerational transmission of gender roles (ITGR). Based on the bioecological theory, this study conducted a paired survey of adolescents (generation 2 [G2]) and their parents (generation 1 [G1]), and explored the ITGR in different family structures, examining the influence mechanism of various factors in the family microsystem on ITGR. Results: Both in single-parent families and two-parent families, the distribution of gender-role types of G2 is similar to that of G1, and the distribution of undifferentiated and androgyny in the two generations is bipolar. In single-parent families, the proportion of undifferentiated is the highest in both G1 and G2, and is significantly higher than that in two-parent families. In two-parent families, the proportion of androgyny is the highest in both G1 and G2, which is significantly higher than that of single-parent families. Family socioeconomic status, family structure, and parental child-rearing gender-role attitudes as three family environment factors, as well as the gender and age of children as two individual factors, significantly influence ITGR. The mediating analysis shows parental child-rearing gender-role attitude plays a mediating role in the influence of family structure on ITGR.